1992
DOI: 10.1620/tjem.166.135
|View full text |Cite
|
Sign up to set email alerts
|

The Diuretic Effect of Calcium Entry Blockade in Normals and Hypertensive Patients.

Abstract: Calcium entry blockers have been shown to exert hemodynamic and diuretic effects in the kidney. The diuretic effects can be demonstrated most clearly in the isolated perfused kidney, not influenced by compensatory mechanisms such as a lower blood pressure or changes of hormones. However, they can also be shown in vivo in humans. We studied the renal effects of calcium entry blockade after the first dosage and after continued oral dosages of 20 mg nicardipine tid in patients with essential hypertension and in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…For example, as mentioned above, short-term administration of felodipine has been demonstrated to both increase and decrease natriuresis and diuresis, depending on the dose administered [44]. However, most reports have indicated that patients maintained on CCBs for chronic therapy exhibited increases in sodium and water excretion that may contribute to their antihypertensive effects [69,70].…”
Section: Renal Effectsmentioning
confidence: 99%
“…For example, as mentioned above, short-term administration of felodipine has been demonstrated to both increase and decrease natriuresis and diuresis, depending on the dose administered [44]. However, most reports have indicated that patients maintained on CCBs for chronic therapy exhibited increases in sodium and water excretion that may contribute to their antihypertensive effects [69,70].…”
Section: Renal Effectsmentioning
confidence: 99%